Atom-Chip Designs for a Trapped and Guided Matterwave Sagnac Interferometer - Johnson, Jamie (2021)
Matterwave interferometers have seen much progress over the last two decades, their use in precision measurements and fundamental physics has been the motivation behind this. However, these interferometers, while having substantial potential advantages over their optical counterparts due to the wave nature of atoms, also suffer a simultaneous drawback for the same reason. Atoms are incredibly sensitive to external effects and perturbations; this makes it hard to isolate atoms from the environment whilst leaving them sensitive to the effect of interest. Also, of particular challenge is the task of trapping and dynamically controlling atoms while keeping them coherent. Atom interferometers have typically relied on free-space propagation, limiting the amount of time available for interrogation. The next stage in atom interferometers is an entirely trapped, guided, and dynamically controlled system; this limits wave packet dispersion and allows for longer interrogation time by design. In this thesis, progress in constructing a radio-frequency dressed, trapped and dynamically controlled, matterwave Sagnac interferometer on an atom-chip will be discussed. Along with this, many current design limitations and solutions to these will be presented.